Virtual consulting in the times of COVID-19 - Latika Gupta; Supriya Sharma; Rajat Kharbanda; Shelley Aggarwal; Durga Prasanna Misra; Vikas Agarwal (Indian Journal of Rheumatology)
Background: Confinement and economic uncertainty, along with disease-specific issues such as pain and suffering may uniquely impact rheumatology patients, putting non-COVID morbidity at par with COVID-related losses. Methods: We conducted a review of records to explore the clinical profile and interventions in rheumatology patients at a tertiary care center in Northern India to identify the potential problems and propose direction for the future. Results: In our experience spanning 5 weeks, among 508 rheumatology patients who sought teleconsultations, rheumatoid arthritis was the most common diagnosis (35.2'), and 43' were asked to continue the same treatment over tele consults, whereas investigations were awaited for another 16'. Nearly one-third (29.9') required an intervention, though this largely consisted of dose titrations (104 of 152, 68.4'). Certain diseases such as myositis were under-represented among consults (1.2') but over-represented (33.3') among admissions. Among the 54 patients who were asked to rate their teleconsultation experience, the voice and consultation quality were rated and average of 9.9 each, and 88.9' (48/54) said they would prefer teleconsultations until the pandemic is over. Conclusion: A sizeable proportion of rheumatology patients can be managed with teleconsultations, with some requiring greater assistance, calling for a triage protocol for the times ahead. With propositions for a deliberate transition into the realm of virtual consulting, chronic caregivers can hope to reach an optimal balance between e-consults and in-person visits.